A hybrid model of modified constraint induced movement therapy to improve upper extremity performance in children with unilateral upper extremity paresis: Retrospective case series - Lee, Gina Kim; Pascual, Marielle; Rethlefsen, Susan A (The British journal of occupational therapy, 2021)
Introduction The study aims were to assess impact of an intensive camp-based intervention using a hybrid model of modified constraint induced movement therapy with bimanual therapy in children with upper extremity impairment, and to see if improvements persisted over time. Method Twenty subjects participated. Eight subjects attended camp 2 years in a row, and 12 subjects attended camp only 1 year. The Assisting Hand Assessment and Children’s Hand-use Experience Questionnaire were administered before and after camp. Assisting Hand Assessment and Children’s Hand-use Experience Questionnaire scores were compared between assessments using linear mixed effects models, adjusting for covariates (age and Manual Ability Classification System level) and the repeated measures within subjects. Results Assisting Hand Assessment score improved during the intervention phase for subjects at all Manual Ability Classification System levels (p ≤ 0.0001). Improvement was maintained long-term at 1 year post. Children’s Hand-use Experience Questionnaire scores for grasp efficacy and time taken were significantly improved during intervention but not maintained at 1 year post. The feeling bothered dimension showed no significant change over time. Conclusion A hybrid model of modified constraint induced movement therapy and bimanual therapy was effective in improving bimanual function for children with varying levels of neurologic hemiparesis, with changes maintained long-term.